Persepsi Mahasiswa PBA terhadap Skripsi Berbahasa Arab di IAIN Syaikh Abdurrahman Siddik Bangka Belitung - Areta Fitriani; Angga Angga; Peni Apriyanti (AL-MUARRIB: JOURNAL OF ARABIC EDUCATION, 2022)
This research is a quantitative research. The purpose of this study was to determine the perception of each individual from the PBA student towards the Arabic Thesis. Perception is the view that each individual has. The research instrument used in this study was a likert scale with total of 33 valid statements. With a random sampling technique as many as 34 students. The analysis used is descriptive statistical analysis. The result of this study are dominant average 38, 24 PBA students agree with the Arabic Thesis.